Pengelompokan Provinsi Berdasarkan Kualitas Jaringan Internet Dengan Metode Centroid Linkage - Dzikrullah, Abdullah Ahmad (Journal of Mathematics, Computations and Statistics, 2022)
After the current pandemic, the internet has shown its power as a medium for digital acceleration and economic transformation. Internet quality is absolutely an essential requirement in carrying out various activities. Indonesia has unequal internet quality, and only specific areas in Java and Sumatra have good quality. This study aims to classify 34 provinces in Indonesia based on five indicators of internet network quality. The cluster method can rank regions based on internet quality indicators. The centroid Linkage method is an object grouping method that has advantages in handling outlier data. This study resulted in four groups with low internet quality located in Papua and West Papua provinces. The contours and topography of the area are obstacles for the government to distribute quality internet.